Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
J. Vercruysse, Bibliographie des écrits français relatifs à Voltaire, 1719-1830 André G. Bourassa, Polémique et propagande dans Rome sauvée et Les Triumvirs de Voltaire O. R Taylor, La Henriade: a complementary note R. J. Howells, The Metaphysic of nature: basic values and their application in the social philosophy of Rousseau R. G. Saisselin, Rousseau and portraiture: from representation to fiction Norma Perry, A Forged letter from Frederick to Voltaire C. Kiernan, Helvétius and a science of ethics Jean A. Perkins, Irony and candour in certain libertin novels R. L. Myers, Rémond dialogues Norma Perry, John Vansommer of Spitalfields: Huguenot, silk-designer, and correspondent of Voltaire Harriet Dorothy Rothschild, Benoît de Maillet's letters to the marquis de Caumont